Multidisciplinary development of the Geriatric Core Dataset for clinical research in older patients with cancer: A French initiative with international survey. (November 2018) - Paillaud, E.; Soubeyran, P.; Caillet, P.; Cudennec, T.; Brain, E.; Terret, C.; Etchepare, F.; Mourey, L.; Aparicio, T.; Pamoukdjian, F.; Audisio, R.A.; Rostoft, S.; et al.
Abstract: Background: To define a core set of geriatric data to be methodically collected in clinical cancer trials of older adults, enabling comparison across trials. Patients and methods: Following a consensus approach, a panel of 14 geriatricians from oncology clinics identified seven domains of importance in geriatric assessment. Based on the international recommendations, geriatricians selected the mostly commonly used tools/items for geriatric assessment by domain (January–October 2015). The Geriatric Core Dataset (G-CODE) was progressively developed according to RAND appropriateness ratings and feedback during three successive Delphi rounds (July–September 2016). The face validity of the G-CODE was assessed with two large panels of health professionals (55 national and 42 international experts) involved both in clinical practice and cancer trials (March–September 2017). Results and discussion: After the last Delphi round, the tools/items proposed for the G-CODE were the following: (1) social assessment: living alone or support requested to stay at home; (2) functional autonomy: Activities of Daily Living (ADL) questionnaire and short instrumental ADL questionnaire; (3) mobility: Timed Up and Go test; (4) nutrition: weight loss during the past 6 months and body mass index; (5) cognition: Mini-Cog test; (6) mood: mini-Geriatric Depression Scale and (7) comorbidity: updated Charlson Comorbidity Index. More than 70% of national experts (42 from 20 cities) and international experts (31 from 13 countries) participated. National and international surveys showed good acceptability of the G-CODE. Specific points discussed included age-year cut-off, threshold of each tool/item and information about social support, but no additional item was proposed. Conclusion: We achieved formal consensus on a set of geriatric data to be collected in cancer trials of older patients. The dissemination and prospective use of the G-CODE is needed to assess its utility. Highlights: The Geriatric Core Dataset (G-CODE) is a minimum set of geriatric data to be collected in cancer trials. The G-CODE was developed after a Delphi consensus method with international agreement. The G-CODE has ten tools/items and a median completion time of 9 min. The G-CODE allows for a minimal geriatric description of the older cancer population. The G-CODE allows standardisation of geriatric data, enabling comparison across trials.